Proceedings of ‏The 3rd International Conference on Advanced Research in Education, Teaching and Learning 2020
DOI: 10.33422/3rd.aretl.2020.12.110
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards ICT: a statistical analysis of gender differences in Spanish higher education teachers

Abstract: The use of ICT resources in the teaching and learning process, as well as in the field of educational research, requires positive attitudes from all higher education teachers. Therefore, the purposes of this study are: (1) to measure both the level of attitude of teachers towards technology related to the teaching and learning process and the level of attitude towards technology related to research in both genders; and (2) to know if there are differences in the attitudes of teachers according to their gender.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…65% in the Australian cohort). This imbalance could have had an impact on the comparisons made in this study as the literature has reported gender-related differences in the attitude toward using Information and Communication Technology according to gender ( 79 81 ). The experience of studying Human Pathophysiology also differed between the two cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…65% in the Australian cohort). This imbalance could have had an impact on the comparisons made in this study as the literature has reported gender-related differences in the attitude toward using Information and Communication Technology according to gender ( 79 81 ). The experience of studying Human Pathophysiology also differed between the two cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…ERE, a branch of distance education, was obligatory during the pandemic (Bozkurt & Sharma, 2020;Hodges et al, 2020). ERE differs from pre-planned experiences designed to be online in that the teaching delivery is temporarily transferred to an alternative mode of delivery due to the circumstances of the crisis (Hodges et al, 2020;Guillén-Gámez et al, 2020) stated that cognitive, affective, and behavioral dimensions compose attitude which is defined as positive, negative, or neutral perceptions and beliefs about a specific issue. Numerous studies have been done to evaluate the students' attitude towards online learning and scales have been developed and validated to measure the students' readiness to participate in online education (Brooks & Grajek, 2020;Chen et al, 2017;Chung et al, 2020;Joo et al, 2018;Romero Martínez et al, 2020;Tzivinikou et al, 2020;Ullah et al, 2017;Zhou, 2016;Zhu et al, 2020;Tzafilkou et al, 2021) reported that the previous measurement models are based on theories such as the Technology Acceptance Model, but have not been adopted to the remote education which is an urgent need in the current pandemic.…”
Section: Rlamentioning
confidence: 99%
“…In the same vein, Akpunonu and Agbarakwe (2021) made a similar discovery in a study conducted in University of Port Harcourt. In a similar study on attitude towards ICT use by Spanish higher education teachers, it was however discovered that there is a significant gender difference in attitude towards the use of technology in teaching and learning in favour of males (Guillen-Gamez, et al 2020). Majority of students in a Malaysian university also show high level of satisfaction with the introduction of Google Classroom tools in in their learning environment (Alssager & Nasir, 2021).…”
Section: Introductionmentioning
confidence: 99%